3PC-019 Cost optimisation on the preparation of antineoplastic and immunomodulating drugs at the hospital pharmacy cpu. (2nd March 2018) - Gonçalves, S; Frade, P; Afonso, R
Abstract : Background: The preparation of antineoplastic agents is a responsibility of the hospital pharmacy and is usually performed at a centralised preparation unit (CPU) to enable better protection for the staff and better safety for the patient. The CPUs have led to standardisation of techniques, implementation of a quality system and also a better use of antineoplastic agents. Those agents are prepared at a vertical laminar flow hood and some of the drugs, especially innovative treatments, have very high costs with significant financial impact for the hospital budget and the National Health System. In an attempt to minimise costs, we have established, among other organisational measures, specific days for the preparation of some of those drugs. Purpose: To evaluate the financial impact associated with the definition of specific days for the preparation of some antineoplastic and immunomodulating drugs at the hospital pharmacy CPU. Material and methods: This prospective, observational and descriptive study took place during May 2017. The drugs included in the study were: bortezomib, liposomal doxorubicin (DLP), bevacizumab, trastuzumab pemetrexed, nivolumab and cetuximab. We took into account the real and the expected costs for each preparation of these drugs, as well as the savings per day and drug, as a result of the spared. We used the Microsoft Excel 7.0 program to collect and analyse data. Results: Bortezomib (€5.360) and bevacizumab (€2.194) were the drugs with the highest impact in total cost savings, with a 24% reduction in the expected costs. For nivolumab the saving was €3.700 (-6%), trastuzumab €2.440 (-8%), DLP €1.600 (-14%), pemetrexed €704 (-7%) and cetuximab €165 (-2. 5%). In one month the saving was €16.163, which represents an 11% reduction in this medicines' expected costs. According to this data, we estimate an €193.956 annual saving. Conclusion: The definition of specific days for the preparation of high-cost treatments is a strategy with a significant impact on waste reduction as well as on human and financial resources' management. An annual saving perspective of approximately €2 00 000 obtained from a single procedural change applied to only seven drugs proved to be highly impactful, especially for its potential use on other drugs and its impact on economical sustainability. No conflict of interest